Common Causes of Vaginal Infections in Women with Vaginal Discharge Attending the Outpatient Clinics of the Maternity Teaching Hospital in Erbil - Zahida Haris Saeed; Nisreen Jasim Mohammad; Runak Ali Ismail; Samira Salim Shekh Mohammad (Diyala Journal of Medicine, 2019)
Background: Vaginal infections are common gynecological problem of women attending consultancy clinics.